Determining the reverse fault current by the type of transformer and Distributed Generation in distribution system during the single-line to ground fault - Cho, Namhun; Yun, Sangwon; Jung, Jaesung (Renewable and Sustainable Energy Reviews, 2019)
Recent increases in Distributed Generation (DG) into distribution system have led to changes in the conventional protection scheme because of the reverse fault current coming from the DG side. However, it is not yet clear whether the reverse fault current is caused by the type of interconnection transformer or the type of DG. Therefore, for reliable coordination between protective devices, it is necessary to analyze the reverse fault current contribution from the DG side to fault location according to the system configuration. In this paper, the single-line to ground fault current contribution is analyzed when different combinations of the transformer and DG are interconnected in the system. For this, a methodology for calculating the fault current according to the type of transformer and DG is introduced. Using this methodology, the fault current contribution from each transformer and DG is analyzed separately to eliminate the mixed contribution from both the transformer and DG. The mixed fault current contribution from the different combinations of these devices is then analyzed. For the interconnection transformer, delta-grounded wye (D-Yg), Yg-Yg, and Yg-D transformer configurations are considered; for DG, synchronous machine-based and inverter-based DG are considered. Based on this analysis, the present paper provides effective guidelines for determining the reverse fault current according to the type of transformer and DG in the distribution system, enabling reliable protection coordination under the integration of DG.
Keywords: D-yg transformer; Distribution systems; Fault current contribution; Inverte-based distributed generation; Inverter-based; Reverse faults; Synchronoi machine-based distributed generation; Synchronous machine; Yg-D transformer; Yg-yg transformer; D-Yg transformer; Fault current contribution; Inverter-based DG; Synchronous machine-based DG; Yg-D transformer; Yg-Yg transformer